Male victims of sexual abuse and domestic violence: A steadily increasing phenomenon. (January 2021) - Margherita, Manuela; Franceschetti, Lorenzo; Maggioni, Lidia; Vignali, Giulia; Kustermann, Alessandra; Cattaneo, Cristina
Violence perpetrated on male victims is a phenomenon that is currently underestimated by both national and international scientific communities, since males are historically (and stereotypically) considered the perpetrators rather than the victims of violence. As a consequence, the available literature lacks data which would allow a better understanding of this issue and its presenting features. We undertook a retrospective analysis of 231 medical files of male victims of violence over a five-year-period (2014–2018) at the Soccorso Violenza Sessuale e Domestica Centre in Milan, Italy. The sample included 112 victims of sexual violence and 119 victims of domestic violence, most of whom were younger than 18 years of age. The main aim of this study was to describe the presentations of male victims of violence in order to understand the phenomenon better, increase awareness of the issue and enable improved health-care management. The need to pay more attention to this vulnerable part of the population is mandatory in health-care services, and it includes: the provision of management guidelines, training to attending physicians and a supportive service to male survivors. Understanding which risk factors are related to male abuse can help with the development of programmes that identify, prevent and minimise violence – this being especially useful for primary-care clinicians. This is the first Italian study to deal with domestic and sexual violence involving male victims.